Case Report: Whole exome sequencing identifies compound heterozygous variants in the TRAPPC9 gene in a child with developmental delay - Yu, Bingxuan; Chen, Jing; Yang, Shuo; Wang, He; Xiao, Yuanyuan; Liu, Shanling (Frontiers in Genetics, 2024)
Background: Developmental delay (DD) in children under 5 years old, which occurs globally with an incidence of 10% to 15%, is caused by multiple factors including genetics, prenatal conditions, perinatal complications, postnatal influences, social factors, and nutritional deficiencies. Gene variants such as EFNB1, MECP2 and TRAPPC9 play a significant role in protein deformation and downregulation of nuclear factor κB (NF-κB) activity. Methods: A 3-year-old girl, who exhibits poor gross motor skills, personal-social development, auditory language, hand-eye coordination, and visual performance, was diagnosed with global developmental delay (GDD). Trio whole exome sequencing was conducted to identify the genetic etiology of her condition. The identified genetic etiology was then validated through Sanger sequencing and quantitative polymerase chain reaction (qPCR). Results: Genetic analysis revealed that the patient had compound heterozygous variants in the TRAPPC9 gene. Both variants were not reported in other studies. These include a novel c.1928del frameshift variant inherited from the unaffected father and a deletion in exon 12 inherited from the unaffected mother. According to the American College of Medical Genetics (ACMG) guidelines, these variants were classified as "likely pathogenic".The study revealed that compound heterozygous TRAPPC9 gene variants cause developmental delay in a Chinese girl. These variants have been classified as having significant pathogenic effect according to the ACMG criteria, suggesting a recessive genetic pattern and highlighting the importance of prenatal testing for future offspring. Furthermore, our findings expand the genotype spectrum of the TRAPPC9 gene, and provide more comprehensive information regarding genetic counseling for children experiencing developmental delay.